Laboratory essays on solid residues from an area of sand mining activities at Analandia, São Paulo, Brazil, and implications to the water resources quality - Bonotto, Daniel Marcos [UNESP]; Oliveira, E. G. (Wit Press, 2004)
This investigation reports the results of tests performed in a laboratory with solid waste samples from an area belonging to Sibelco Mineracao Ltd., which is located around Analandia municipality, nearly in the center of São Paulo State, Brazil. Dissolution and leaching essays were realized under different experimental conditions in four samples collected from the mining front and decantation pool, with the aim of evaluating the possibility of release of several constituents to the liquid phase.
Keywords: sand mining; effluents; solid waste classification; leaching and dissolution experiment; water quality; ground water; surface water; anthropogenic activity; elemental concentrations; trace and heavy metals